INTERNATIONAL ISLAMIC BANKS’ POPULARITY AMIDST THE ASEAN ECONOMIC COMMUNITY: INSIGHTS FROM INDONESIA AND MALAYSIA - Bawana, Tate Agape; Mansor, Fadillah; Noordin, Kamaruzaman (Bank Indonesia, 2024)
The establishment of the ASEAN Economic Community (AEC) aimed to achieve regional integration among all ASEAN member states, with particular emphasis on financial integration. Islamic banking is in line with the broader goals of the AEC, as an alternative financial system, helping to build a more resilient and inclusive financial system in the region. Because of this resiliency and inclusiveness, Islamic banks have been encouraged to develop into international banks in the ASEAN region through increasing their assets and earnings. This paper aims to examine the position of International Islamic banks (IIb) in the AEC under its conventional banking services: OCBC Bank from Singapore, Maybank and CIMB Bank from Malaysia. Through the analysis of banking trends, this qualitative study compares the level of popularity of those banks in Indonesia and Malaysia, the two Muslim-majority countries in ASEAN, after the initial establishment of the AEC period in 2016 to 2024. The findings indicated that the most popular Islamic financial services in Malaysia are provided by Maybank, while the most well-known Islamic financial services under IIb in Indonesia are provided by CIMB Bank. This paper provides an overview of the globalisation of IIb in ASEAN and fills a research gap on the development of IIb, particularly within the AEC.